Dibutyl phthalate release from polyvinyl chloride microplastics: Influence of plastic properties and environmental factors. (1st October 2021) - Yan, Yuanyuan; Zhu, Fengxiao; Zhu, Changyin; Chen, Zhanghao; Liu, Shaochong; Wang, Chao; Gu, Cheng
Highlights: Factors affecting DnBP release from PVC microplastics were systematically studied. More phthalate was released from microplastics with higher phthalate content. Natural aging of plastics led to changed phthalate release. Coexistence of fulvic acid and NaCl had a greater effect on phthalate release than fulvic acid alone. Leaching of surface-active DOC from plastics could promote the release of phthalate plasticizer. Abstract: In recent years, great efforts have been made to understand the capacity of microplastics to adsorb environmental pollutants; however, relatively little is known about the ability of microplastics to release inherent additives into peripheral environments. In this study, we investigated the leaching behavior of phthalate plasticizer from polyvinyl chloride (PVC) microplastics, in aqueous solutions relevant to aquatic and soil environments. It was found that plastic properties, such as particle size, plasticizer content and aging of plastics had a great effect on the leaching of dibutyl phthalate (DnBP). Phthalate release was generally higher in smaller particles and particles with higher phthalate content. Whereas, plastic aging caused by solar irradiation could either enhance phthalate release by increasing plastic hydrophilicity or decrease the leaching by reducing readily available fractions of phthalate. Regarding environmental factors, solution pH (3–9) and ionic strength (0–0.2 M NaCl) were found to have minor effect on phthalate release, while fulvic acid (0–200 mg/L) greatly promoted the release by improving phthalate solubility and solution-plastic affinity. Interestingly, we found that more DnBP was leached out when fulvic acid and NaCl coexisted, and the results from dissolved organic carbon (DOC) and three-dimensional fluorescence spectroscopy analyzes suggested that the leaching of other fulvic acid-like additives might have played a role. These findings would be helpful for predicting the potential of microplastics to release toxic additives under different environmental conditions. Graphical abstract: Image, graphical abstract